Author Correction: Lymphoblastoid cell lines from Diamond Blackfan anaemia patients exhibit a full ribosomal stress phenotype that is rescued by gene therapy. Issue 1 (December 2018) - Aspesi, Anna; Monteleone, Valentina; Betti, Marta; Actis, Chiara; Morleo, Giulia; Sculco, Marika; Guarrera, Simonetta; Wlodarski, Marcin; Ramenghi, Ugo; Santoro, Claudio; Ellis, Steven; Loreni, Fabrizio; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.